Calibration of cast-in fibre Bragg gratings for internal strain measurements in cast aluminium by using neutron diffraction. (15th October 2020) - Heilmeier, Florian; Koos, Robert; Hornberger, Peter; Hiller, Jochen; Weraneck, Klaus; Jakobi, Martin; Koch, Alexander W.; Volk, Wolfram
Graphical abstract: Highlights: Fiber Bragg Gratings (FBG) are cast into aluminium parts as internal strain sensors. In-situ strain evolution during cast process is investigated for two cast alloys. Strain data obtained by FBG-measurements is validated by neutron diffraction. FBG strains correlate with straining of the Al(311) crystallite for all specimens. FBG strain rates offer enhanced knowledge about solidification characteristics. Abstract: Fibre Bragg gratings (FBGs) are utilized to function as internal strain sensors during casting, solidification and cooling of two hypoeutectic Al alloys and technically pure Al. In situ neutron diffraction experiments were conducted simultaneously onsite the STRESS-SPEC instrument at the Research-Neutron Source (MLZ) in Garching. The experimental data correlated with structural finite element simulation and X-ray micro tomography (CT) elucidates the mechanisms of this measurement system. The presented work offers a new practical approach to measure in-situ strains during casting of Al alloys by using FBG-based sensors. The FBG strain results correlate with the Al(311) peak obtained by neutron diffraction which is furthermore used for calibration. The examination of interactions between fibres and surrounding cast Al by finite element simulation and CT of the cast specimens enables the application of the sensors for unequivocal strain measurements in castings as well as the characterization of alloys during solidification.